If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -7) = 6(x + -9) + 60 Reorder the terms: 4(-7 + x) = 6(x + -9) + 60 (-7 * 4 + x * 4) = 6(x + -9) + 60 (-28 + 4x) = 6(x + -9) + 60 Reorder the terms: -28 + 4x = 6(-9 + x) + 60 -28 + 4x = (-9 * 6 + x * 6) + 60 -28 + 4x = (-54 + 6x) + 60 Reorder the terms: -28 + 4x = -54 + 60 + 6x Combine like terms: -54 + 60 = 6 -28 + 4x = 6 + 6x Solving -28 + 4x = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -28 + 4x + -6x = 6 + 6x + -6x Combine like terms: 4x + -6x = -2x -28 + -2x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 -28 + -2x = 6 + 0 -28 + -2x = 6 Add '28' to each side of the equation. -28 + 28 + -2x = 6 + 28 Combine like terms: -28 + 28 = 0 0 + -2x = 6 + 28 -2x = 6 + 28 Combine like terms: 6 + 28 = 34 -2x = 34 Divide each side by '-2'. x = -17 Simplifying x = -17
| 1x+2y=60 | | N/24=4/9 | | 0.7xX=29820 | | 8-0.03w=1.8 | | 3(x+4)=x-3 | | 3v+13=40 | | M^2=-49 | | 20+-3(2x+-7)=5(x+5)+-6 | | 9x+4=4x+9 | | 5/18=6/x | | (3x^2+4x-3)=(4x^2-3x+2) | | 10-3(2x-7)=5(x+5)-6 | | -7(x+1)=13 | | y-4=4*(1+0) | | -2(x-4)=3x+6-1x | | 12=a/5-4 | | 13(x-1)=7x+23 | | 15x=18+13x | | 13y+36=153 | | 8(4s+9)=328 | | -3x-6/4=3 | | y^2-xy-3x=1 | | 1/6x-9=-2 | | 2x-21=5x-3y-12 | | (2x-7)+(3x+4)=0 | | 10x^4=0.001 | | (7/4)(-5) | | 15p+p+-19p+20p+-14p-16=-2 | | 8r+2r-2r-3r-3r=20 | | -5n-(-14n)+-11n+-4n=18 | | 2(x-4)-3(5x-1)=8 | | 7j+6j-12j=17 |